Learning versus the Common Core - Tampio, Nicholas (Forerunners: Ideas First, 2019)
An open challenge to Common Core's drive for uniformity Nicholas Tampio watched as his kindergartner's class shifted from one where teachers, aides, parents, and students worked hard to create a rewarding educational experience to one in which teachers delivered hours-long lectures using packaged lesson plans. Learning versus the Common Core explains how standards-based education reform is transforming nearly every aspect of public education by looking closely at the standards, the agenda of people pushing standards-based reform, and how these fit within a global pattern of education reform. With a nod to the philosophy of John Dewey, Tampio concludes with a vision of what democratic education can look like today-and how people can form rhizomatic alliances across different political and ethical backgrounds to fight the Common Core. Forerunners: Ideas First Short books of thought-in-process scholarship, where intense analysis, questioning, and speculation take the lead